Iowa RBA, May 22-24, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for May 22-24, 1995. Highlights of the update include sightings of Glossy Ibis, White-faced Ibis, two nests of Barn Owls, Whimbrel, Common Moorhen and a Red-necked Phalarope. Epson - sheet feed/flatbed